Relevansi Islamic Worldview dalam Disiplin Ilmu Ekonomi Islam - Rosyidah, Fahmi; Fitriani, Laili; Amriati, Ulil; Fahriani, Aulia Nurul; Sumiran, Sumiran (Lembaga Yasin AlSys, 2026)
Although the concept of Islamic economics has been the focus of various previous studies, research that specifically examines the relevance of the Islamic worldview in the discipline of Islamic economics remains relatively limited. This study aims not only to describe Islamic economics but also to analyze in detail how the Islamic worldview is relevant to the discipline of Islamic economics. It employs a qualitative approach with a library research design and descriptive analysis. The findings show that the discipline of Islamic economics is highly relevant to the Islamic worldview because it possesses an epistemological foundation rooted in revelation and its validity has been scientifically tested. Islamic economic theory is derived from the Qur'an and Hadith, while its economic philosophy is sourced from religion (ad-diin). In addition, Islamic economics simultaneously encompasses two disciplines, namely economics (Iqtishad) and fikih muamalah. This study extends the analysis of Islamic economics, contributes theoretically to enriching the literature on Islamic economics, and has practical implications for various related stakeholders. It also opens opportunities for further exploration of the relevance of the Islamic worldview in Islamic economics in the contemporary modern era.